Pašlì baby atavaû… Baba ǔ parèmìâh garadzenskìh belaruskih gavorak - Konczewska, Katarzyna (Słowiańska frazeologia gwarowa II, 2020)
THE CONCEPT OF BABA IN THE PAREMIAS OF THE BELARUSIAN DIALECTS OF THE GRODNO REGIONThe article presents the implementation of the lexeme baba in Grodno Belarusian dialects. The analysis was made based on dialect materials of the entire period of study of the region. The article presents the history of research dialects and folklore in the region of Grodno, primary sources the paper and focuses on the negative connotations of the lexeme baba.